Le Pôle d’accueil universitaire Séolane de Barcelonnette : analyse qualitative d’un tourisme scientifique entre expérimentation et médiation montagnardes - Alain Schoeny (Revue de Géographie Alpine)
The Séolane is a university centre that welcomes tourists and researchers, some of whom are on holiday. Located in Barcelonnette, a French town in the Alpes-de-Haute-Provence region, this unique tourist attraction featuring scientific culture has led the centre’s researchers to conduct a social experiment and scientific mediation in close connection with their professional environment. In order to answer the question of the cultural, psychological and social function of this research, this article presents a constructivist and systemic epistemological approach to social representations that are based on the human experience of participating in tourism and the research missions at the centre. Through documenting this scientific activity by means of qualitative analysis, this paper posits that the Séolane’s scientific tourism opens up a line of questioning on responsible mountain tourism that has not yet been researched within the framework of a transition to recreational use.